2018
DOI: 10.1002/jpen.1315
|View full text |Cite
|
Sign up to set email alerts
|

ThedaCare Nutrition Risk Screen Improves the Identification of Non–Intensive Care Unit Patients at Risk for Malnutrition Compared With the Nutrition Risk Screen 2002

Abstract: The ThedaCare NRS improves the identification of patients at risk for malnutrition in the non-intensive care unit hospital setting. This trial was registered at www.clinicaltrials.gov as NCT02585245.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Second, TGH implemented and evaluated a suite of hospital-wide QI interventions targeted to the needs of the organisation. Previous literature has demonstrated the promise of targeted interventions,16–21 25–28 but few articles have evaluated an institution-wide, multipronged model for detecting deficiencies in malnutrition care and implementing changes to address them. This study offers a unique assessment of the implementation of such a strategy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, TGH implemented and evaluated a suite of hospital-wide QI interventions targeted to the needs of the organisation. Previous literature has demonstrated the promise of targeted interventions,16–21 25–28 but few articles have evaluated an institution-wide, multipronged model for detecting deficiencies in malnutrition care and implementing changes to address them. This study offers a unique assessment of the implementation of such a strategy.…”
Section: Resultsmentioning
confidence: 99%
“…A number of recent studies demonstrating successful results of QI programmes focused on malnutrition were published in a supplement to the Journal of the Academy of Nutrition and Dietetics that can be accessed at https://jandonline.org/issue/S2212-2672(19)X0003-9. While many studies evaluate the ability of specific screening tools to correctly identify malnutrition risk, few assess treatment and follow-up care activities 16–21. Studies looking at the impact of specific nutrition interventions have shown positive effects of an interdisciplinary care team developing and implementing a comprehensive nutrition care and discharge plan 8 14…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was estimated based on the malnutrition rates in patients with cirrhosis of 44•6 % assessed by the NRS-2002 and 50•7 % assessed by the RFH-NPT (16) . The reported sensitivity and specificity of nutritional risk screening by the NRS-2002 vary widely, with values of 50-86 and 21-93 %, respectively (23) . The calculated minimum sample size was 96, with a sensitivity and specificity of 50 %, an α of 0•05 and a power of 85 % (24) .…”
Section: Sample Size Estimationmentioning
confidence: 99%
“…Malnutrition is defined as any nutritional imbalance, which is a major complication in hospitalised patients and increases the length of stay (LOS), healthcare costs and mortality (7)(8)(9)(10)(11) . The prevalence of malnutrition is 15-80 % in hospitalised patients, while only 3 % could be diagnosed and treated (8,12) . It has been reported that over 40 % of CKD patients are undernourished (13) and uraemia and dialysis can impact the nutritional status of patients with kidney disease (14,15) .…”
mentioning
confidence: 99%